Living Near Oil Palm Plantations: Students' Environmental Literacy by Gender and Grade Level - Wulandari Saputri; Meli Astriani; Siti Nurhayati; Setia Budi; Nurkhairo Hidayati (Postgraduate, University of Mataram, 2025)
Indonesia is the world's largest palm oil producer, but this industry presents environmental challenges such as deforestation, biodiversity loss, and pollution. Enhancing students’ environmental literacy, particularly those living near oil palm plantations, is key in fostering ecological awareness. This study aims to analyze students' environmental literacy levels based on gender and grade level at Puspita Senior High School, South Sumatra. This research employs a descriptive design using a survey method with an environmental literacy questionnaire measuring knowledge and attitudes toward environmental issues. The study involved 244 students categorized by gender and grade level. Data were analyzed using descriptive statistical techniques and the Kruskal-Wallis test to determine differences in environmental literacy across variables. The findings indicate that students’ overall environmental literacy is very good, with an average score of 54.36. There is no significant difference in environmental literacy between male and female students, although females scored slightly higher in attitude. Similarly, no significant difference was found based on grade level. Factors such as an inclusive curriculum, uniform learning experiences, and students' residential environment near oil palm plantations are believed to contribute to these findings. In conclusion, students living near oil palm plantations exhibit high environmental literacy, with no significant differences based on gender or grade level. These results highlight the importance of equitable environmental education in fostering ecological awareness among young generations.